Decontamination of cyst (Globodera spp.) infested potato seed tubers with sodium hypochlorite (NaOCl) - BAIRWA, AARTI; SHARMA, SANJEEV; VENKATASALAM, E P; SHARMA, ASHWANI KUMAR; MHATRE, PRIYANK H; SINGH, R K; CHAKRABARTI, S K (The Indian Journal of Agricultural Sciences, 2020)
Potato cyst nematode (Globodera spp.) is one of the serious pests of potato worldwide including India. Infested seed tubers and soil are the primary means of spread of cysts to non-infested areas, whereas air, water, human, animals, field equipments, composts, gunny bags are other means of spread. Therefore, a study was carried out with different concentrations of NaOCl under in vitro and in vivo condition to see its decontamination effect on potato cyst nematode (PCN). The results revealed that potato tubers harvested from the PCN infested fields can be completely decontaminated by giving dip treatment in NaOCl (2%) solution for 30 min. and the treated tubers sprouts normally after two months of storage.